(untitled) (Palíndromo, 2019)
The attempt of part of contemporary art production to promote different kinds of collective experiences can be considered as a specific desire of being together. Thus, the present text, as part of a broader study of the “being together” forms in contemporary art, intends to focus on a specific form presents in several works of art. It is the “encounter”. The purpose is to pay attention to works of art that explore the “encounter” as a device for the “being together” forms. In this regard, were analysed specific works by artists like Marina Abramovic, collective OPAVIVARÁ!, Ana Teixeira, Eleonora Fabião and Anna Costa e Silva.